The policy reassembly of Afghanistan's higher education system. (1st January 2019) - Couch, Daniel
ABSTRACT: This paper explores how a national higher education sector can be assembled upon a relatively narrow ideological foundation during and in the aftermath of violent conflict. It analyses the case of Afghanistan's higher education system, and argues that the violent disintegration of this system during the 1980s and 1990s created the conditions for a neoliberal reassembly and subsequent expansion of higher education from 2001. This paper draws on data gathered from document analysis, and semi-structured interviews with key policy actors. It identifies an ideological grounding in neoliberalism within higher education policies which are responsible for directing the sector's growth since 2010. I argue that this neoliberal agenda, largely driven by globalised influences, has exploited Afghanistan's conflict-affected context to position higher education primarily as a driver of economic growth, thus limiting policy emphasis on higher education's non-economic dividends. The paper concludes by critiquing the underlying assumption that this role is sufficient if higher education is to serve as a key institution in Afghanistan's ongoing national development.